2017
DOI: 10.1016/j.neulet.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the corticospinal tract within the porcine spinal cord: Implications for experimental modeling of traumatic spinal cord injury

Abstract: Spinal cord injury (SCI) researchers have predominately utilized rodents for SCI modeling and experimentation. Unfortunately, a large number of novel therapies developed in rodent models have failed to demonstrate efficacy in human clinical trials which suggests that improved animal models are an important translational tool. Recently, porcine models of SCI have been identified as a valuable intermediary model for preclinical evaluation of promising therapies to aid clinical translation. However, the localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Although the tracer injections likely labeled a limited number of cortical neurons, thousands of CST axons were present at C2 and traveled down to the thoracic spinal cord indistinctly of their cortical origin. These results confirm that pigs have a complete pyramidal system with cortico-bulbar and corticospinal components, in agreement with recent studies in swine that found CST axons descending along the complete cervical spinal cord after injection of anterograde tracers in M1 (Leonard et al, 2017). Our results likewise confirm and extend the suggestion that PM contributes corticospinal axons (Bech et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the tracer injections likely labeled a limited number of cortical neurons, thousands of CST axons were present at C2 and traveled down to the thoracic spinal cord indistinctly of their cortical origin. These results confirm that pigs have a complete pyramidal system with cortico-bulbar and corticospinal components, in agreement with recent studies in swine that found CST axons descending along the complete cervical spinal cord after injection of anterograde tracers in M1 (Leonard et al, 2017). Our results likewise confirm and extend the suggestion that PM contributes corticospinal axons (Bech et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Studies on axonal Wallerian degeneration ensuing M1 lesion in domestic pigs led to the conclusion that the porcine CST was essentially inexistent, the pyramidal tract consisting only of cortico-bulbar axons that innervated cranial motoneurons and ended at the pyramidal decussation ( Palmieri et al, 1987 ). This notion prevailed for two decades until it was re-addressed by injecting anterograde neural tracers in M1 ( Leonard et al, 2017 ), showing that porcine CST axons travel along the complete cervical spinal cord. Also using anterograde tracers, Bech et al (2018) found that about 86% of the porcine CST fibers crossed in the pyramidal decussation and descended by the contralateral dorsolateral fasciculus of the upper cervical spinal cord, and suggested that the premotor cortex may contribute CST axons.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to rodents, where the rubrospinal tract is predominantly involved. These anatomical and functional similarities to humans provide support for pigs as a reliable animal model for preclinical research into traumatic SCI (Leonard et al, 2017). In general, it should be noted that both small and large animal models of SCI have limitations in their ability to predict outcomes in human SCI (Rosenzweig and McDonald, 2004;Bassols et al, 2014).…”
Section: Experimental Animals Used In Sci Studiesmentioning
confidence: 94%
“…They share similar anatomical and physiological characteristics with humans, particularly the cardiovascular, urinary, reproductive and digestive systems (Bassols et al, 2014). In the pig spinal cord, the localization of the corticospinal tract (CST) inside the lateral columns of the white matter is more similar to humans than to rodents (Leonard et al, 2017). In terms of anatomical function, the CST plays a key role in locomotion of the pigs' hindlimbs.…”
Section: Experimental Animals Used In Sci Studiesmentioning
confidence: 99%
“…Even though huge progress has been made in the preclinical field in the understanding of the tSCI pathophysiology, in the identification of therapeutically relevant targets, and in the development of molecular, cellular, and technology-supported therapies, none of these approaches has reached approval as a standard therapy [ 8 ]. Among many reasons for this are (i) general low translational value of rodent models, (ii) different neuroanatomical features of rodent and human spinal cord such as different locations of the corticospinal tracts, (iii) the usage of SCI lesion models with little relevance for human SCI, for example, the wire knife transection model [ 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%